PENTINGNYA PENGENDALIAN SUPPLY BAHAN BAKU DALAM AKTIVITAS PROSES PRODUKSI PADA RUMAH SUSTAINABLE ASSEMBLY PADA INDUSTRI RUMAH DI JABON SIDOARJO - Mufaridah, Ennis; Suhartini, Fiskha (Jurnal Ilmu Manajemen Advantage, 2018)
Home industry that has been the backbone of local government, always in galakkan to improve the dignity of society of lower economic class which generally become small business actor, in business activity important factor to be considered is controlling raw material, so easy to be controlled and not damaged then the amount of raw materials to be purchased in accordance with the needs, so that it can be minimized the amount of raw materials that tend to be damaged. Thus, raw materials purchased can be efficient for production process activities.